2018
DOI: 10.36722/sh.v4i1.248
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Religiusitas Terhadap Penerimaan diri Orangtua Anak Autis di Sekolah Luar Biasa XYZ

Abstract: <p><em>Abstrak</em><em> - </em><strong>Riset ini bertujuan untuk mengetahui pengaruh religisitas dan penerimaan diri orang tua dari anak autis di SLB XYZ di Bekasi. Setiap orang tua menginginkan anaknya dapat lahir dan tumbuh secara sempurna, namun ketika kenyataan yang harus dihadapi tidak sesuai dengan harapan, seringkali orang tua menyalahkan Tuhan dan tidak mau menerima keadaan anaknya.</strong><strong> </strong><strong>Penerimaan diri (<em>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 2 publications
1
2
0
4
Order By: Relevance
“…The analysis results of gender in nine articles showed that men were the majority of respondents compared to women, because autism was 4 times more common in men. These findings are in line with research (Rahmawati, 2018) which states that autism is more common in boys than girls with a ratio of 3:1 or 4:1. The reason is hormones, men produce more testosterone and women produce more estrogen (Astuti & Maria, 2019; Wati et al, 2020).…”
Section: Resultssupporting
confidence: 92%
“…The analysis results of gender in nine articles showed that men were the majority of respondents compared to women, because autism was 4 times more common in men. These findings are in line with research (Rahmawati, 2018) which states that autism is more common in boys than girls with a ratio of 3:1 or 4:1. The reason is hormones, men produce more testosterone and women produce more estrogen (Astuti & Maria, 2019; Wati et al, 2020).…”
Section: Resultssupporting
confidence: 92%
“…When the individual is able to make peace with the situation at hand, the individual will look at himself in a positive and realistic way. If someone sees himself consistently, he will try to acknowledge and accept his deficiencies, not be saddened by the situation, and try to change his condition to better and get a healthy life [15].…”
Section: Discussionmentioning
confidence: 99%
“…Penerimaan diri adalah sikap yang pada dasarnya merasa puas dengan milik sendiri, kualitas dan bakat sendiri, dan pengakuan akan keterbatasan diri sendiri, sikap yang menunjukkan rasa puas terhadap dirinya sendiri, baik kekurangan maupun kelebihannya, sehingga dapat membentuk harapan yang realistis terhadap dirinya dan menghargai dirinya sendiri (Rahmawati, 2017). Di sisi lain Riff dalam (Afra & Elyta, 2017) menambahkan bahwa tidak hanya perasaan puas terhadap diri sendiri melainkan sikap positif terhadap diri sendiri, baik tentang apa yang terjadi di masa kini maupun masa lalu.…”
Section: Penerimaan Diriunclassified

Untitled

Fadillah,
Purbaningrum,
Nurul Hidayati
2024
SETARA